A Review of Fiqh Muamalah on the Practice of Unsecured Credit in Conventional Banking - Hidaya, Taufik; Fatimah, Siti (Zabags Qu Publish, 2025)
Unsecured Loans (KTA) are conventional banking products that offer loans without requiring collateral or guarantees. While providing easy access to financing, this practice raises several issues from the perspective of Fiqh Muamalah, particularly concerning contracts (akad), riba (usury), gharar (uncertainty), and fairness in transactions. This study aims to analyze the compliance of KTA practices in conventional banking with the principles of Fiqh Muamalah. Using a descriptive qualitative approach and literature review, the study found that KTA practices generally contain elements of riba through the application of interest on loans and gharar in additional fees that lack transparency. These findings indicate potential injustice and inconsistency with Shariah values, which emphasize fairness, transparency, and freedom from riba. The implication of this research is the need for more appropriate Shariah-compliant financial product innovations, such as using Murabahah, Ijarah, or Qardhul Hasan contracts as alternatives to conventional KTA. The novelty of this study lies in its critical analytical approach to KTA practices by integrating Fiqh Muamalah principles and providing concrete solutions to enhance Shariah compliance in banking products.